Chromatin subunits from baker's yeast: isolation and partial characterization. - Nelson, D A (1977)
The organization of proteins along DNA in chromatin of Saccharomyces cerevisiae (baker's yeast) was examined by analyzing the DNA and nucleoprotein products obtained after digestion of yeast nuclei with staphylococcal nuclease. Yeast DNA is digested in situ at regularly spaced cleavage sites about 160 base pairs apart. Nucleoprotein fragments were resolved and isolated by centrifugation on linear, 5-20% sucrose gradients. The predominant 11S component appears to be identical to chromatin "subunits" or "nucleosomes" isolated from higher eukaryotes, containing a 150-160 base pair length of DNA and approximately equimolar amounts of four proteins that coelectrophorese with calf histones H2A, H2B, H3, and H4, plus small amounts of three proteins that electrophorese similarly to H1 histones. Thus, the structural organization of the yeast genome is similar to that of more developed organisms, except for the smaller total repeat length. None of the yeast subunit proteins, including the possible H1 proteins, contains cysteine.